Escherichia coli isolates from femoral bone marrow of broilers exhibit diverse pheno- and genotypic characteristics that do not correlate with macroscopic lesions of bacterial chondronecrosis with osteomyelitis. Issue 3 (4th May 2018) - Gaußmann, Barbara; Hess, Claudia; Grafl, Beatrice; Kovacs, Mercedes; Troxler, Salome; Stessl, Beatrix; Hess, Michael; Paudel, Surya
ABSTRACT: The pheno- and genotypic relatedness among Escherichia coli isolates from broilers with and without macroscopic lesions of the femoral head were investigated. In total, 219 isolates obtained from the bone marrow were characterized by serotyping, antimicrobial resistance (AMR) profiles, phylogenetic grouping, detection of virulence-associated genes (VAGs) and pulsed-field gel electrophoresis (PFGE). Serotyping revealed that 48.4% of the isolates were assigned to one of the three serotypes (O78:K80: 21.0%, O2:K1: 18.7%, O1:K1: 8.7%). Substantial phenotypic variation was also noticed in AMR testing as most of the birds harboured E. coli isolates with different AMR profiles, which is of high clinical relevance. The majority of isolates could be classified into phylogenetic groups D (54.3%) and B2 (25.6%), followed by A (11.4%) and B1 (8.7%). Virulotyping showed that the highest number of isolates contained genes iuc D (86.8%) and iss (84.9%), whereas pap C (16.0%) and ast A (12.3%) were present in least number of isolates. PFGE resulted in 58 different profiles from 200 typeable isolates. No correlation was found between specific serotypes, AMR profiles, phylogenetic groups, PFGE types or VAG profiles of E. coli and the occurrence of bacterial chondronecrosis with osteomyelitis, contradicting the hypothesis of a specific bacterial pheno- or genotype being involved in the disease.